The influence of joint technologies on ELV recyclability. (October 2017) - Soo, Vi Kie; Compston, Paul; Doolan, Matthew
Highlights: Separation efficiency was measured for ELV parts through an industrial trial. Characterised the influence of joining techniques on separation efficiency. Identified joining methods that maximise separation efficiencies in ELV recycling. Identified initial correlation between joint types and the presence of impurities. Identified initial correlation between joint types and valuable material losses. Abstract: Stricter vehicle emission legislation has led to the increasing use of lightweight materials and multi-material concepts to reduce the vehicle mass. To account for the complexity of multi-material vehicle designs, the choice of joining techniques used is becoming more diverse. Moreover, the different material combinations, and their respective joining methods play an important role in determining the potential of full material separation in a closed-loop system. This paper evaluates the types of joining technologies used in the automotive industry, and identifies those that hinder the sorting of ELV materials. The study is based on an industrial shredding trial of car doors. Observations from the case study showed that steel screws and bolts are increasingly used to combine different material types and are less likely to be perfectly liberated during the shredding process. The characteristics of joints that lead to impurities and valuable material losses, such as joint strength, material type, size, diameter, location, and protrusion level, can influence the material liberation in the current sorting practices and thus, lead to ELV waste minimisation. Additionally, the liberation of joints is also affected by the density and thickness of materials being joined. Correlation analyses are carried out to further support the influence of mechanical screws and bolts on material separation efficiencies. The observations are representative of the initial phases of current global ELV sorting practices.